Prison Leave in Finland: Legal and Empirical Fundamentals of an Established Practice - Keinänen, Anssi (European journal on criminal policy and research, 2020)
Prison leave was introduced into the Finnish legal system in 1971, with the aim to reduce negative effects of institutionalization and disadvantages caused by the length of the prison sentence. After the total reform of prison legislation in 2006, the role of the prison leave has become even more central; the number of prisoners has decreased, but the amount of prison leave has increased. Historically, the length of the sentence has been the most common ground for prison leave. A prisoner can be granted a prison leave when two thirds of the prison term has been served, for example, after 2 years if the length of the total sentence served in prison is 3 years. However, during the past 10 years, prison leave based on an important reason has grown into the most common type of prison leave. This indicates a structural change from the rigid legal rules to a more flexible practice. In 2018, there were about 17,000 prison leave applications, and over 13,000 of those were granted, i.e. 79%. The conditions were breached 466 times, which is 3.5% of all prison leaves. The most common breaches of prison leave conditions were returning from a prison leave after the set time limit or under the influence of alcohol or drugs. The majority of prison leave applications are decided in the prisons. On the other hand, for example, the decision on the prison leave of a life-sentenced prisoner is made by the Criminal Sanctions Agency. There have been significant differences in the probability of granting prison leave, which are emphasized especially in the practices of closed prisons. Among those prisoners who serve longer than 1 year in prison, the application rate of prison leave rises over 90%. For the sentences under 3 months, it is less than 20%.